A Full-Length Reference Floral Transcriptome of Boehmeria tricuspis Provides Insights into Apomeiosis and Polyploidy. (17th December 2019) - Tang, Qing; Xu, Ying; Deng, Canhui; Cheng, Chaohua; Dai, Zhigang; Yang, Zemao; Liu, Chan; Su, Jianguang
Abstract : Boehmeria tricuspis (Hance) Makino constitutes a hardy herbaceous or shrubby perennial native to East Asia that includes different ploidy levels and reproductive modes (diplosporous to sexual). Although several apomeiosis-associated genes have been described, the genetic control and molecular mechanisms underlying apomeiosis remain poorly understood. Moreover, the basis of the correlation between polyploidy and apomixis has not yet been clarified. We utilized long-read sequencing to produce a full-length reference floral transcriptome of B . tricuspis . Based on the generated database, gene expression of the female flowers of different ploidy levels and reproductive mode cytotypes was compared. Overall, 1, 387 genes related to apomeiosis, 217 genes related to ploidy, and 9 genes associated with both apomixis and ploidy were identified. Gene Ontology analyses of this set of transcripts indicated reproductive genes, especially those related to "cell differentiation" and "cell cycle process, " as significant factors regulating apomeiosis. Furthermore, our results suggested that different expressions of stress response genes might be important in the preparation for apomeiosis transition. In addition, our observations indicated that the expression of apomeiosis may not depend on polyploidy but rather on deregulation of the sexual pathway in B . tricuspis .